ISLAMIC LAW REVIEW OF RIBA IN THE PRACTICE OF ARISAN - ismatul azimah (Jurnal Ilmiah Pesantren, 2021)
Arisan is a form of contemporary muamalah which basically consists of two functions, namely as a means for savings and accounts receivable debt. The arisan that develops in society today is of various forms and mechanisms so it is not uncommon for people to use arisan as a place for profit. This research was conducted to find out how the practice of arisan today, whether with the development of the current arisan model has the potential of riba in it. The research method used is library research, the discussion in this research uses descriptive qualitative analysis, then the data are analyzed to draw a conclusion. The results of this research indicate that the law of social gathering in Islam is basically mubah, but it is illegal when in practice there is a riba element namely the addition of the acquisition of each member who is not the same and has been determined at the beginning of the agreement. Found many elements of riba in the practice of arisan that developed at this time even with riba being a special attraction in the community